Pengaruh Adopsi Fintech, Literasi Keuangan, Digital Marketing, Inovasi Produk dan Modal Usaha terhadap Kinerja UMKM : (Studi pada UMKM di Desa Kalampa Kecamatan Woha) - Asdiansyuri, Ulfiyani; Octavia, Yusi Faizatul (Sekolah Tinggi Ilmu Ekonomi AMM, 2025)
This study aims to determine the influences that can affect the development of MSMEs in Kalampa Village. This type of research is quantitative. The sampling technique used in this study is a random sampling technique. The research sample was 49 Business Actors in Kalampa Village, Woha District. The test results show that partially fintech adoption, financial literacy, digital marketing, product innovation and business capital have a positive effect on MSMEs performance. With fintech adoption implemented, adequate financial literacy, MSMEs owners can identify and manage financial risks more effectively, thereby protecting the business from potential losses. By implementing Digital Marketing, MSMEs can expand market reach, increase interaction with customers, and build strong brand awareness. Product innovation allows MSMEs to create or develop products that are in accordance with market needs and trends, thereby increasing business competitiveness. Meanwhile, business capital provides the financial support needed to fund operational activities, production, and business development. The influence of the variables Fintech Adoption, Financial Literacy, Digital Marketing, Product Innovation, and Business Capital (independent variables) on MSMEs performance (dependent variable) is 71%, while the remaining 29% is contributed by other variables not included in the study, such as access to capital, work productivity, technology implementation, entrepreneurial orientation, and marketing access.